Penerapan Menyusun Instrumen Penilaian Afektif Di SMPN 2 Ponorogo - farida amalina fahrulloh; Dina Novitasari; Ellyza Trisna Ramadhani; Elyza Devi Pramesti; Eva Alfiyatu Zahro' (https://ejournal.insuriponorogo.ac.id/, 2024)
Affective assessment is the most important part of learning. In assessing student attitudes, teachers use instruments by creating a table consisting of student names and attitudes as a whole, without reference to assessment guidelines (rubrics). This study highlights the steps of affective assessment guidelines at SMPN 2 Ponorogo starting from determining the aspects to be assessed to the scoring stage. The main purpose of writing and researching this article is to explain the affective assessment guidelines so that they are in line with the demands of the curriculum that emphasizes the importance of character development and moral values in education. So that it can improve the quality of education and achieve educational goals. The method used in this writing is a type of survey research with a qualitative approach and descriptive method. There are 2 sources of data taken, namely primary data sources from interviews with SMPN 2 Ponorogo teachers and secondary data sources through references in obtaining data. In-depth study of books, journals, and other sources. using reference data sources in the form of books, journals and other sources.Keywords : affective,assessment, steps